(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Cognitive disorders, including dementia and Alzheimer's disease, pose substantial global health challenges, demanding effective prevention and treatment strategies. Intermittent Hypoxia Therapy (IHT), involving brief exposures to reduced oxygen levels, is a novel approach with potential cognitive benefits. This study investigates the effects of Intermittent Hypoxia Therapy (IHT) on cognitive behavior in Wistar albino rats through comprehensive behavioral experiments, including the Open Field Test (OFT) and Morris Water Maze (MWM). The results reveal that IHT promotes locomotor activity, reduces anxiety-related behaviors, and positively impacts cognitive flexibility. In the OFT, the IH group exhibited increased grid crossings and distance traveled, indicating heightened locomotion, which may be associated with cognitive improvement. Furthermore, IH significantly reduced thigmotaxis behavior and the number of fecal boli, indicating reduced anxiety levels compared to the control group. While IHT did not significantly enhance spatial memory acquisition in the MWM, it improved platform recognition during the probe test. The IH group spent more time in the target quadrant, suggesting enhanced memory retrieval and recognition. Additionally, in the reverse MWM, IH demonstrated moderate improvements in cognitive flexibility, with faster latency on trial 1. These findings suggest that IHT holds promise as a non-invasive intervention for cognitive enhancement, particularly in terms of locomotor activity, anxiety reduction, and certain aspects of memory and cognitive flexibility. Further research is warranted to elucidate the underlying mechanisms and explore the potential therapeutic applications of IHT in cognitive disorders. In summary, this study highlights the cognitive benefits of IHT in rats, paving the way for future investigations and potential clinical applications in the realm of cognitive disorders.